Product traits, decision-makers, and household low-carbon technology adoptions: moving beyond single empirical studies. (January 2022) - Schulte, Emily; Scheller, Fabian; Pasut, Wilmer; Bruckner, Thomas
Abstract: Although single empirical studies provide important insights into who adopts a specific LCT for what reason, fundamental questions concerning the relations between decision subject (= who decides), decision object (= what is decided upon) and context (= when and where it is decided) remain unanswered. In this paper, this research gap is addressed by deriving a decision framework for residential decision-making, suggesting that traits of decision subject and object are determinants of financial, environmental, symbolic, normative, effort and technical considerations preceding adoption. Thereafter, the decision framework is initially verified by employing literature on the adoption of photovoltaic systems, energy efficient appliances and green tariffs. Of the six proposed relations, two could be confirmed (financial and environmental), one could be rejected (effort), and three could neither be confirmed nor rejected due to lacking evidence. Future research on LCT adoption could use the decision framework as guidepost to establish a more coordinated and integrated approach, ultimately allowing to address fundamental questions. Highlights: Decision subject and object are equal parts of residential adoption behavior. Decision framework suggests that traits of decision subject and object predict the evaluation of the object. Proposed relations for financial and environmental considerations confirmed. Blind spots concerning normative and technical considerations.